ANALISIS PENERAPAN METODE PETA KONSEP PADA MATA PELAJARAN IPS KELAS VII SMP ISLAM TERPADU MIFTAHUL ULUM - Hendra Rustantono; Nafisatul Hasanah (Jurnal Education and Development, 2023)
The problem raised in this study is the analysis of the use of the concept map method in social studies learning in class VII SMP IT Miftahul Ulum. This study aims: 1) To find out how to plan using the concept map method in learning in class VII at SMP IT Miftahul Ulum. 2) To find out how the implementation of using the concept map method in Social Studies Learning in class VII at SMP IT Miftahul Ulum 3) To find out how to evaluate using the concept map method in Social Studies Learning in class VII at SMP IT Miftahul Ulum. This type of research is a type of descriptive qualitative research, namely research that aims to describe the results of the research found by the author at the research site. The data collection techniques were using interviews, observation and documentation. The results of this study state that: 1) Planning using the concept map method, the teacher prepares lesson plans, Prota, Promes and Syllabus, lessons and materials needed during learning, exemplifies how to make Concept Maps and prepares tools, media, materials and teaching materials needed in the teaching process. 2) There are 3 implementations when using the concept map, namely Demonstration, Individual and Group. 3) Evaluation when using the concept map IPS teachers conduct written tests, projects and make summaries.